Practice Guidelines for Primary Care of Acute Abdomen 2015. (21st December 2015) - Mayumi, Toshihiko; Yoshida, Masahiro; Tazuma, Susumu; Furukawa, Akira; Nishii, Osamu; Shigematsu, Kunihiro; Azuhata, Takeo; Itakura, Atsuo; Kamei, Seiji; Kondo, Hiroshi; Maeda, Shigenobu; Mihara, Hiroshi; et al.
Abstract : Since acute abdomen requires accurate diagnosis and treatment within a particular time limit to prevent mortality, the Japanese Society for Abdominal Emergency Medicine, in collaboration with four other medical societies, launched the Practice Guidelines for Primary Care of Acute Abdomen that were the first English guidelines in the world for the management of acute abdomen. Here we provide the highlights of these guidelines (all clinical questions and recommendations were shown in supplementary information). A systematic and comprehensive evaluation of the evidence for epidemiology, diagnosis, differential diagnosis, and primary treatment for acute abdomen was performed to develop the Practice Guidelines for Primary Care of Acute Abdomen 2015. Because many types of pathophysiological events underlie acute abdomen, these guidelines cover the primary care of adult patients with nontraumatic acute abdomen. A total of 108 questions based on nine subject areas were used to compile 113 recommendations. The subject areas included definition, epidemiology, history taking, physical examination, laboratory test, imaging studies, differential diagnosis, initial treatment, and education. Japanese medical circumstances were considered for grading the recommendations to assure useful information. The two‐step methods for the initial management of acute abdomen were proposed. Early use of transfusion and analgesia, particularly intravenous acetaminophen, were recommended. The Practice Guidelines for Primary Care of Acute Abdomen 2015 have been prepared as the first evidence‐based guidelines for the management of acute abdomen. We hope that these guidelines contribute to clinical practice and improve the primary care and prognosis of patients with acute abdomen. Abstract : Highlight Mayumi and colleagues present the first English‐language evidence‐based guidelines for primary care of acute abdomen, developed by the Japanese Society for Abdominal Emergency Medicine in collaboration with four other medical societies. The guidelines provide recommendations for specific primary management of acute abdomen with 108 clinical questions and a two‐step flowchart.